Analisis Pengaruh Tarif Pelayanan GoRide Pada Applikasi Gojek Terhadap Loyalitas Pelanggan - Erlisa Aulia; Dhiwa Humaira Ninvika; Yolanda Junita Sari; Indah Apsari Asmana Nurfitriani (Peneliti.net, 2023)
Transportation at this time has become a part of the need for every human being where the mode of transportation makes all human activities easier and more effective in time. Along with the development of science, technology and information, people innovate to combine the world of transportation with the internet so that what is called online transportation is formed. Gojek is an online transportation technology company from Indonesia that serves transportation through motorcycle taxi services. This company was founded in 2010 in Jakarta by Nadiem Makarim. Currently, Gojek is available in 50 cities in Indonesia. However, in the midst of the progress of Gojek, many online motorcycles taxi platform competitors have emerged that provide the same features and services at a cheaper rate that can affect customer loyalty to Gojek services. The purpose of this research is to determine the effect of GoRide feature service rates on the Gojek application on customer loyalty from Jakarta State University Students. The population of this study is all Gojek customers from Jakarta State University Students and 100 respondents were sampled. The method used is the quantitative method by distributing questionnaires to UNJ students who use the GoRide feature in the Gojek application. The results in the study show that the quality of service and tariffs are quite influential on customer loyalty and have a good positive and significant side influence, so Gojek should pay more attention to the quality of service, especially at which rates which are still quite affordable for customers.